Venous thromboembolism in Latin America: a review and guide to diagnosis and treatment for primary care (Clinics, 2016)
There are various region-specific challenges to the diagnosis and effective treatment of venous thromboembolism in Latin America. Clear guidance for physicians and patient education could improve adherence to existing guidelines. This review examines available information on the burden of pulmonary embolism and deep vein thrombosis in Latin America and the regional issues surrounding the diagnosis and treatment of pulmonary embolism and deep vein thrombosis. Potential barriers to appropriate care, as well as treatment options and limitations on their use, are discussed. Finally, an algorithmic approach to the diagnosis and treatment of venous thromboembolism in ambulatory patients is proposed and care pathways for patients with pulmonary embolism and deep vein thrombosis are outlined for primary care providers in Latin America.